Intraoperative assessment of ureter perfusion after revascularization of transplanted kidneys using intravenous indocyanine green fluorescence imaging - Potchara Kanammit (2022)
Background: Kidney transplantation is the most valuable renal replacement therapy. One of the most common urologic complications following kidney transplantation is ureter anastomosis leakage, which leads to high morbidity along with kidney graft loss. We hypothesized that indocyanine green (ICG) fluorescence videography can assess ureter perfusion after revascularization of transplanted kidneys. Methods: We conducted a prospective cross-sectional study in end-stage renal disease patients who underwent deceased donor kidney transplantation at Ramathibodi Hospital from September 2019 to January 2020. The segments of transplanted ureters were categorized as having good or poor perfusion based on the percentage from ICG fluorescence videography images. Then the results from ICG fluorescence videography were compared with histopathology which is considered the gold standard. Results: Thirty-one sections of dissected ureters were evaluated from 10 patients. Compared with pathological diagnosis of ureteral ischemia, ICG videography had sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and positive likelihood ratio of 100%, 92.6%, 66.7%, 100%, and 14, respectively. Accuracy was 93.6%. The area under the curve of ICG fluorescence videography was 0.96. The average ureter length that maintained good perfusion was 14 cm from the ureteropelvic junction. Adverse events from ICG were not observed in this study. Conclusions: We conclude that ICG fluorescence videography is beneficial for detection of early ureteral ischemia in kidney transplantation patients, with negligible adverse events. However, further studies with larger numbers of patients are necessary to confirm our results and clinical outcomes regarding complication rates.